Mixed Matrix Problems in the Theory of Representations - Gubareni, Nadiya (Sarajevo Journal of Mathematics, 2019)
In this paper we consider flat mixed matrix problems, i.e. the problems of reducing a family of matrices by some family of admissible transformations. We present some examples of flat matrix problems of unbounded representation type which are considered over a discrete valuations ring with a skew field of fractions and its skew field extension of the second degree.